ENT 530 Social Media Portfolio: Scented Memories / Nurafiza Mustapa - Mustapa, Nurafiza (2020)
Scented Memories is a business that offers quality products for many customers namely air freshener. Reasonable prices and quality products are accessible to all customers who purchase our products. Target audience for Scented Memories is especially for all individuals who have a car and face car odor problems. Various types of fragrances for air fresheners offered to meet the needs of customers. On November 2020, scented memories have started operating online. Sales are done online to facilitate the purchase and payment. Facebook page is used to promote Scented Memories products and create higher sales. Our business also holds alluring sales promotions to engage many customers to buy our products. Product promotion is done using teaser, soft sell, and hard sell to gain more sales and customers.